Exploring common pathogenic association between Epstein Barr virus infection and long-COVID by integrating RNA-Seq and molecular dynamics simulations - Kanwal, Ayesha; Zhang, Zhiyong (Frontiers in Immunology, 2024)
The term “Long-COVID” is characterized by the aftereffects of COVID-19 infection. Various studies have suggested that Epstein-Barr Virus (EBV) reactivation is among the significant reported cause of Long-COVID (LC). However, there is a lack of in-depth research that could largely explore the pathogenic mechanism and pinpoint the key genes in EBV and LC context. This study, mainly attributed to predict the potential disease associated common genes between EBV reactivation and LC condition using NGS data and reported the naturally occurring biomolecules as an inhibitor. We applied the bulk RNA-Seq from LC and EBV-infected peripheral blood mononuclear cells (PBMCs), identified the differentially expressed genes, protein-protein interaction (PPI) network using STRING database followed by the hub genes identification using cytoscape plugins Cytohubba and MCODE followed by enrichment analysis using ClueGO. The interaction analysis of a hub-gene was performed against naturally occurring bioflavonoids molecules using molecular docking and molecular dynamics simulations (MDS) method. Out of 357 common genes, 22 genes (CCL2, CCL20, CDCA2, CEP55, CHI3L1, CKAP2L, DEPDC1, DIAPH3, DLGAP5, E2F8, FGF1, NEK2, PBK, TOP2A, CCL3, CXCL8, DEPDC1, IL6, RETN, MMP2, LCN2, and OLR1) were classified as hub genes, and the remaining were filtered as neighbouring genes. Enrichment analysis showed the role of hub genes in various pathways such as immune-signalling pathways, including JAK-STAT signalling, interleukin signalling, protein kinase signalling, and toll-like receptor pathways associated with the symptoms reported in the LC condition. ZNF and MYBL TF-family were predicted as the abundant TFs controlling hub-genes' transcriptional machinery. Further, OLR1 (PDB: 7XMP) showed the stable interactions with the five short listed refined naturally occurring bioflavonoids i:e Apigenin, Amentoflavone, Ilexgenin A, Myricetin and Orientin compounds. The total binding energy pattern was observed and found that Amentoflavone was the top docked molecule (binding affinity of –8.3 Kcal/mol ) with the lowest total binding energy -18.48 Kcal/mol. In conclusion, our research has predicted the hub genes, their molecular pathways, and the potential inhibitors between EBV and LC potential pathogenic association. The in-vivo or in-vitro experimental methods could be utilized to functionally validate our findings which would be helpful to cure the Long-COVID or to prevent EBV reactivation.